2014
DOI: 10.3109/13506129.2014.900486
|View full text |Cite
|
Sign up to set email alerts
|

Plerixafor-augmented peripheral blood stem cell mobilization in AL amyloidosis with cardiac involvement: a case series

Abstract: Nearly half of AL amyloidosis patients have cardiac involvement, an independent predictor of poor prognosis. High-dose melphalan and autologous stem-cell transplantation (HDM/SCT) can induce complete hematologic responses and prolong survival in AL amyloidosis. Granulocyte colony-stimulating factor (G-CSF)-induced mobilization of peripheral blood stem cell (PBSC) in AL amyloidosis patients is associated with volume overload, arrhythmias and capillary leak syndrome. Plerixafor has a different mechanism of actio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 21 publications
1
4
0
Order By: Relevance
“…In a phase II study, plerixafor combined with G‐CSF was shown to be efficient for CD34 mobilization and allowed for fewer apheresis sessions in patients with lymphoma and multiple myeloma . Several other small case series have highlighted the safety and efficacy of plerixafor‐based stem cell mobilization in AL amyloid patients . Our center adopted a combined G‐CSF/plerixafor‐based stem cell mobilization in patients with AL amyloidosis with the goal of reducing G‐CSF and enhancing CE in AL amyloidosis.…”
Section: Introductionsupporting
confidence: 90%
See 2 more Smart Citations
“…In a phase II study, plerixafor combined with G‐CSF was shown to be efficient for CD34 mobilization and allowed for fewer apheresis sessions in patients with lymphoma and multiple myeloma . Several other small case series have highlighted the safety and efficacy of plerixafor‐based stem cell mobilization in AL amyloid patients . Our center adopted a combined G‐CSF/plerixafor‐based stem cell mobilization in patients with AL amyloidosis with the goal of reducing G‐CSF and enhancing CE in AL amyloidosis.…”
Section: Introductionsupporting
confidence: 90%
“…In terms of post-autoHCT outcomes, the median time to neutrophil recovery was 14 days (range 9-21) and the median time to platelet engraftment was 14 days (range [9][10][11][12][13][14][15][16][17][18][19]. Day 100 transplant-related mortality was 0.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In patients with AL amyloidosis, G-CSF-induced stem cell mobilisation is associated with volume overload, arrhythmias, and capillary leak syndrome. 15 The risk is therefore significant and can occur in patients without amyloidosis with cardiac involvement.…”
Section: Discussionmentioning
confidence: 99%
“…The recommended optimal dose of CD34+ cells in AL patients is at least 5 × 10 6 CD34+ cells/kg [21]. Plerixafor, CXCR4 receptor antagonist, as a stem cell mobilization regimen along with an abbreviated dose of G-CSF can be beneficial in patients with fluid overload to reduce the dose of G-CSF and reduce the risk of capillary leak syndrome and also reduce the number of leukapheresis session needed for optimal stem cell collection yield [22, 23].…”
Section: Stem Cell Mobilization and Collectionmentioning
confidence: 99%